The Services Of General Interest In Romania: Legal And Institutional Aspects At National And Territorial Level - Daniela L. Constantin; Raluca Mariana Petrescu; Claudiu Herteliu; Alina Iosif; Alina Profiroiu (European Regional Science Association (ERSA), 2012)
Before 1990, the services of general interest (SeGI) in Romania were entirely provided by the public authorities. Afterwards, the market was gradually liberalized and the SeGI captured the attention of private operators. Nowadays, the business sector is involved next to the public authorities in offering services of general interest so as to respond citizens' expectations. The cooperation between the public authorities and the business sector is more developed in the area of SeGI that prove to be profitable, such as waste service and public transport, rather than services that need high investments in infrastructure, such as electricity, gas and water supply service. Starting from these overall considerations this paper addresses the legal and institutional issues generated by the organising and the provision of SeGI, with a particular emphasis on the territorial distribution of competences and the derived responsibilities. It takes into consideration the classification of competences associated to local authorities as a result of the decentralisation process, which are divided into exclusive, shared and delegated ones. Two territorial levels are considered, namely the counties - LAU1 (the same as NUTS3) and the localities (municipalities, towns and communes) – LAU 2. The development regions (NUTS2) are not considered as they are not administrative units and, consequently, do not have competences in the administration of the services of general interest. A series of drawbacks, inconsistencies are revealed followed by reflections on the solutions adopted by the authorities in favour of economic liberalisation and sustainable development of the local communities. They are derived from the Law of communitarian services of public utilities no. 51/2006, which is the main pillar of the policy framework for the public services in Romania. Thus, the public services in Romania could be provided by direct and indirect management. The latter might represent the solution that would directly support the cooperation between the local public administration authorities and the business sector and would indirectly generate the liberalization of services of general interest. The paper is based on the research conducted under the auspices of the on-going ESPON project "Indicators and perspectives for services of general interest in territorial cohesion and development – SeGI" (PS 1-16, No.094/2011), in which Bucharest Academy of Economic Studies is one of the partners involved.
Keywords: R12; R58; O18; L8; L9; 330; services of general interest; competences; local administrative units; local development; public – private cooperation